Design and Construction of a DC-to-DC Converter for Electric Vehicle Application - Radwan, Eyad Moh'd (1998)
A DC-to-DC converter has been designed to control the speed of a DC motor for electric vehicle application. The power circuit of the converter consists of transistorised power switches (IGBTs) to step-down the voltage to the level required by the speed and load demand. The series shunt resistor method is used to control the current and keep it below the maximum rate of the power transistors and the motor especially at the starting point. The transistor gate drive circuit was designed to provide the maximum isolation between the power and the control circuits. A controller chip originally used to control a three phase brushless DC motor is programmed and modified to control a brushed DC motor. This controller chip provides the pulse width modulation (PWM) control signal in order to drive the power switches at fixed frequency and variable duty cycle. More over using this chip a control over the current flow through the power circuit could be achieved, this will protect the circuit from any faulty conditions taking the benefit of Cycle-by-Cycle current detection.